(The Effect Of Use Chitosan On Difference For Concentration For Formula Of Skin Lotion) - Rizal Alamsyah; Eddy Sapto Hartanto; Mardiah - (Balai Besar Industri Agro, 2009)
Chitosan is produced commercially in large scale from the other shell of crusteceans as shrimp and crab. At moment chitosan is not used in pharmacy industry but could for other industry as cosmetic, food and beverages,. In cosmetic industry as for skin care preparation like skin lotion, chitosan used for humectant, emulsifier and stabilizer. The aim of this resarch is to study the effect of chitosan as humectant, emulsifier and stabilizer in hand and body lotion formulation. In this experiment, chitosan was added to hand body lotion product wuth several cocentration level e.g. (F1) without chitosan; (F2) 3 ppm of chitosan; (F3) 5 ppm of chitosan; (F4) 10 ppm of chitosan and (F5) 25 ppm of chitosan. Hand and body lotion produced was tested with some testing parameters including homogenity, pH, viscosity, emulsion stability, evaporated and organoleptic for colour, aroma and stickiness. The result showed that the best treatment was F3 (5 ppm of chitosan), the best of homogeneity level, everages pH 6,37, viscosity 1660 cps, evaporation only 78,29 % and organoleptic test score averages was 4,02.